Germline E-cadherin mutations in hereditary diffuse gastric cancer: assessment of 42 new families and review of genetic screening criteria. Issue 7 (2nd July 2004) - Brooks-Wilson, A R; Kaurah, P; Suriano, G; Leach, S; Senz, J; Grehan, N; Butterfield, Y S N; Jeyes, J; Schinas, J; Bacani, J; Kelsey, M; Ferreira, P; et al.
Abstract : Background: Mutations in the E-cadherin (CDH1) gene are a well documented cause of hereditary diffuse gastric cancer (HDGC). Development of evidence based guidelines for CDH1 screening for HDGC have been complicated by its rarity, variable penetrance, and lack of founder mutations. Methods: Forty three new gastric cancer (GC) families were ascertained from multiple sources. In 42 of these families at least one gastric cancer was pathologically confirmed to be a diffuse gastric cancer (DGC); the other family had intestinal type gastric cancers. Screening of the entire coding region of the CDH1 gene and all intron/exon boundaries was performed by bi-directional sequencing. Results: Novel mutations were found in 13 of the 42 DGC families (31% overall). Twelve of these mutations occur among the 25 families with multiple cases of gastric cancer and with pathologic confirmation of diffuse gastric cancer phenotype in at least one individual under the age of 50 years. The mutations found include small insertions and deletions, splice site mutations, and three non-conservative amino acid substitutions (A298T, W409R, and R732Q). All three missense mutations conferred loss of E-cadherin function in in vitro assays. Multiple cases of breast cancers including pathologically confirmed lobular breast cancers were observed both in mutation positive and negative families. Conclusion: Germline truncating CDH1 mutations are found in 48% of families with multiple cases of gastric cancer and at least one documented case of DGC in an individual under 50 years of age. We recommend that these criteria be used for selecting families for CDH1 mutational analysis.